On the Spectral and Energy Efficiency Analysis of Statistical Clustered-Based MIMO Channel - Uri Arta Ramadhani; Purwono Prasetyawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
The Multiple-Input Multiple-Output technology played as the key role in the accomplishment of user high data rate. In the evolution of cellular technology to future wireless communication and beyond, the utilization of millimeter wave has been projected to deliver a better performance in terms of capacity and latency. However, the development of this technology is limited by the system power consumption. In this paper, we study the performance of cellular system using multiple antennas by evaluating the spectral efficiency, throughput, and energy efficiency. The measurements are conducted using a clustered channel model in several different scenarios. The simulation result shows that the performance of the system in UMi type of environment scenario outperforms other scenarios. Furthermore, this work also evaluate the relationship of the spectral and energy efficiency in varying related parameters, including number of antennas and power of the transmitter.